A Review of the Biomass Valorization Hierarchy - Pestana da Paixão Cansado, Isabel (2025)
The sustainability of the planet is based on reducing the use of fossil fuels and greenhouse gas emissions. The recovery of biomass waste puts economically valuable materials into circulation, which can successfully replace fossil fuels and which would otherwise be sent to landfills. Based on the review of several published works, we observe that the referenced processes to value biomass or biomass waste are not necessarily the most profitable and environmentally friendly. The most used methods to valorize biomass and biomass waste are mainly based on researchers knowledge and experience, neglecting some methods that are more appropriate or developing technologies. The valorization of biomass and biomass wastes should promote the production of products with the highest added value, and it must also be environmentally friendly and cost-effective. This manuscript proposes a hierarchy for the use of various valorization processes of biomass waste, from various agricultural activities, urban solids waste, food processing industries, and even wood industries. The proposed hierarchy is based on a number of recommendations aimed at increasing the use and valorization of biomass, in order to reach the objective of carbon neutrality and to comply with the principles of the circular economy.